2016
DOI: 10.2152/jmi.63.58
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gender and body weight on fibroblast growth factor 23 responsiveness to estimated dietary phosphorus

Abstract: Fibroblast growth factor 23 (FGF23) is a molecule involved in regulating phosphorus homeostasis. Although some studies indicated an association between serum FGF23 levels and sex, the association has not been fully investigated. The purpose of this study was to evaluate whether sex could influence FGF23 responsiveness to dietary phosphorus intake in healthy individuals. Thirty two healthy subjects between 21 and 28 years were recruited for this study. Subjects performed 24-hour urine collection and blood sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Age and gender have also been associated with elevated FGF23 [ 54 ]. However, this association remains controversial [ 55 , 56 ]. The increased FGF23 levels in younger patients may reflect higher protein and phosphate intake.…”
Section: Discussionmentioning
confidence: 99%
“…Age and gender have also been associated with elevated FGF23 [ 54 ]. However, this association remains controversial [ 55 , 56 ]. The increased FGF23 levels in younger patients may reflect higher protein and phosphate intake.…”
Section: Discussionmentioning
confidence: 99%
“…Males had slightly higher (non-significant) FGF-23 levels than females, which is similar to the results in human studies. 17,25,30 Given that the estrogen receptor is located in proximal tubules and is important in regulating the structure and function of kidneys, as well as in Pi excretion, 28 it has been suggested that female hormones could inhibit the action of FGF-23. A previous study 9 reported that the RI for FGF-23 in geriatric cats (median age: 13 y old) was 56–700 pg/mL, which was higher than we observed (0–336 pg/mL).…”
Section: Discussionmentioning
confidence: 99%